Ergonomics assessment of drudgery in rice-wheat production system in India: a case study of women farmers - Joshi, Pratibha; Mahra, Girijesh Singh; Jethi, Renu; Satyapriya,; Singh, Rahul; Bishnoi, Sitaram; Sahu, Subhashree; Barua, Sukanya; Sarkar, Sujit; Burman, Rajarshi Roy (Frontiers in Sustainable Food Systems, 2024)
Farm women are often forced to work in extremely hazardous conditions due to their limited access to improved agricultural technologies. This circumstance makes agricultural work physically demanding, requiring significant physiological effort and the maintenance of good posture. It is also very exhausting, time-consuming, and stressful. The study was designed to evaluate and quantify the drudgery involved in the rice-wheat production system for rural women. Three replications of a 10-min work cycle without a break were used to assess the physiological and postural demands of various farm tasks on the female workers. Observations were recorded on farm women workers who were in normal health, without any major illness, and regularly involved in farm operations. In the attempt to obtain and analyze the prioritized drudgery experiences in crop production activities through drudgery assessment and reduction, various ergonomically sound farm tools and implements were provided for crop cultivation and intercultural operations. Data indicating musculoskeletal disorders were analyzed by ergonomics assessment of postural and biomechanical assessments using the Human Physical Drudgery Index (HPDI), resulting in the maximum drudgery reflecting very high risk in transplanting (48.4%), followed by threshing (47.2%), load carrying (46.00%), and harvesting (45.14%). For physiological ergonomics quantifications, the most drudgery-prone activities in the rice-wheat production system, i.e., transplanting, harvesting, threshing & post-harvest, and load carrying, were evaluated, and it was found that drudgery is caused by different activities with reflects working energy expenditure rate ranging from ~7.00 to 12.00 (kJ/min) and total cardiac cost of work (TCCW) ~ 331.00 to 524.00. Multivariate regression analysis was employed to drive relationships between energy expenditure rate (dependent variable) and other independent variables, such as age, body mass index (BMI), mid-upper arm circumference (MUAC), calf circumference (CC), skinfold measurements, body density (D), % body fat, fat mass, and fat-free mass (kg). It was found that energy expenditure rate during various crop production practices is positively correlated with independent variables (R = 0.721, R2 = 0.520, Adjusted R2 = 0.518, Standard Error of Estimate = 0.0324, Durbin-Watson = 1.531). It was found that with higher physiological parameters, the corresponding energy expenditure is maximized relating to the drudgery in respective agricultural activities. The present study addressed the magnitude of drudgery for women farmers in the rice-wheat production system and its mitigation strategy.